Currency devaluations, aggregate demand, and debt dynamics in an economy with foreign currency liabilities - Karsten Köhler (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2016)
The paper employs a post-Kaleckian model to address the question of how currency devaluations affect aggregate demand, capital accumulation, and debt in an economy with foreign currency liabilities. In benchmark post-Kaleckian open economy models currency devaluations have two key effects. First, they change international price competitiveness and thus affect net exports. Second, devaluations change income distribution and thereby affect consumption and investment demand. The overall effect on aggregate demand and investment is ambiguous and depends on parameter values. Existing models, however, disregard balance sheet effects that arise from foreign currency-denominated external debt. The paper develops a novel post-Kaleckian open economy model that introduces foreign currency-denominated external debt and balance sheet effects. The model is then used to analyse the effects of a currency devaluation on aggregate demand, growth, and debt dynamics in small open economies with a fixed exchange rate in the short- to medium-run. The main findings are that the existence of foreign currency-denominated debt means that devaluations are more likely to take a contractionary form, and that foreign interest rate hikes, and high illiquidity and risk premia compromise debt sustainability. Devaluations only stabilise debt ratios if they succeed in boosting domestic capital accumulation.
Keywords: E11; E12; F36; F41; 330; currency devaluation; external debt; balance sheet effects; original sin; currency mismatch; Kaleckian model